Digital marketing counseling as a marketing strategy for MSMEs in facing the Covid-19 pandemic in Manado City - Ade Yusupa; Bernad Jumadi Dehotman Sitompul; Jimmy Reagen Robot (Universitas Muhammadiyah Magelang, 2023)
Several months have passed, the Indonesian economy has weakened due to the Covid-19 pandemic. The number of people who are positive for Covid-19 is increasing, while the community's economic strength is weakening. One strategy that can be utilized by MSMEs is the use of technology in marketing or digital marketing. This activity aims to provide counseling on how to build a digital ecosystem with online marketing or digital marketing during the Covid-19 pandemic outbreak. After the activity, partners are able to recognize digital marketing variants, especially using Google My Business to support the existence of MSMEs in the midst of the Covid-19 pandemic.